METHODOLOGY OF DEVELOPING MEDIA LITERACY COMPETENCIES IN STUDENTS IN THE CONDITIONS OF DIGITAL TRANSFORMATION - Ergasheva Shahnoza Mavlonboyevna (Bright Mind Publishing, 2025)
This article analyzes the role of information technologies and multimedia in the process of providing the population with fast and reliable information in emergency situations and the protocols for their management. The development of digital communication systems, in particular the integrated model of information through mobile networks, Internet protocols, satellite communication systems and social networks, is highlighted. Also, the mechanisms of application of modern protocols such as IoT (Internet of Things), WebRTC, MQTT, SIP and HTTP/2 in emergency notification systems, their advantages and security aspects will be analyzed on a scientific basis. The effectiveness of multimedia media (audio, video, interactive maps and infographics) in informing the population, enhancing visual and emotional impact are also highlighted on the basis of practical examples. The results of the study have an important scientific and practical value for managing the flow of information in emergency situations, ensuring prompt awareness of the population and guaranteeing the continuity of communication.
Keywords: Emergency Awareness, Information Technology, Multimedia, Communication Protocols, WebRTC, MQTT, IoT, Satellite, Message System, Digital Security, Real-Time Data Interchange.